The role of thrombopoietin receptor agonists in the management of adult primary immune thrombocytopenia – a single center experience - Virijević, Marijana; Mitrović, Mirjana; Pantić, Nikola; Pravdić, Zlatko; Sabljić, Nikica; Suvajdžić-Vuković, Nada (Vojnosanitetski pregled, 2022)
Background/Aim. The availability of thrombopoietin receptor agonists (TPO-RA) for treating primary immune thrombocytopenia (ITP) has transformed its management over the last decade. The aim of this study was to assess the efficacy of TPO-RA in adults with chronic ITP treated at the University Clinical Center of Serbia. Methods. A total of 28 adult ITP patients (10 males and 18 females), who were given eltrombopag and/or romiplostim, were enrolled in the study. Data on demographic characteristics, ITP duration, previous therapeutic modalities, comorbidities, concomitant therapy both for comorbidities and ITP, indications for TPO-RA, bleeding episodes before and during TPO-RA, TPO-RA doses, adverse events, and response rates were collected from the patients’ medical records. TPO-RAs were administered in patients with chronic refractory ITP when splenectomy was contraindicated/unfeasible and as preparation for splenectomy. Favorable treatment response was defined as a stable platelet count ≥ 50 × 109/L. Results. A total of 22 (78.57%) and 14 (50.0%) patients were treated with eltrombopag and romiplostim, respectively. A good treatment response (GTR) was achieved in 81.8% of the patients receiving eltrombopag and 71.4% of those treated with romiplostim. The non-responders to eltrombopag (4 patients) and those who had lost their response to eltrombopag (4 patients) were switched to romiplostim. Six of 8 patients achieved a GTR. At the time of TPO-RA initiation, 46.4% of the patients used concomitant ITP therapy, which was ceased in all those with a GTR. The following adverse effects of TPO-RA were registered: transaminitis and transient ischemic attack for eltrombopag – one patient each, and pulmonary embolism in one romiplostim-treated patient. Conclusion. Our study showed that TPO-RAs are an effective and safe treatment option since the majority of patients achieved stable remission without bleeding episodes.